(3TQM dGejI GdYQHs - (3YeQh Hf eGdc GdCROj ; GdTfaQj,J (B70 (3g` s ((3YHO GdHGbi HQSeQ GdCejQ ejQRG eMehONGf s)
(3ChdgG (B:s
(3CbjehG Hf Cei UQhQ eWjce aEf Edi bhe ShGce dCejd s
(3BNQgG (B:s
(3hjQcOf HGdCUGd Lhdi dCfJi ef GdYUe COai jfJMi GdcjM CYbd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3BNQ UaMGJgG JYbjHIs
(3GdCHjGJ GdCNjQI ZjQ eTQhMIs
(3GfXQ fSNJjf CNQJjf HGdeYgO ai GdLRA GdChd HQbei (B693 (3, (B694 (3COHs
(3dGejI GdYQH bUjOg ddTfaQi s
(3hgh YeQh Hf eGdc GdeJhai (B70(3b s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs